2020
DOI: 10.1371/journal.pntd.0008329
|View full text |Cite
|
Sign up to set email alerts
|

The organization, weaknesses, and challenges of the control of thalidomide in Brazil: A review

Abstract: The drug thalidomide has resurged in the world market under restrictive conditions for marketing and use. In Brazil, there are still cases of pregnant women using thalidomide even after the implementation of laws that regulate the control of use (Law No. 10.651/2003 and Collegiate Board Resolution No. 11/2011). The objective of this study was to discuss the control of thalidomide use in Brazil, based on a scoping review of the scientific literature, documents, and data from the Ministry of Health. A total of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, in each suspected case a thorough investigation should be done to exclude other causes of the "Thalidomide embryopathy phenotype". [32][33][34] A scoping review of access to thalidomide in Brazil suggested a need for a national Clinical Protocol and Therapeutic Guidelines for use of thalidomide in ENL cases, uniform accreditation of health centres approved for supply of thalidomide and for a national database of patients treated with it. Brazilian law requires women of childbearing age to use contraceptive precautions when they are prescribed thalidomide.…”
Section: Personal Communication)mentioning
confidence: 99%
“…However, in each suspected case a thorough investigation should be done to exclude other causes of the "Thalidomide embryopathy phenotype". [32][33][34] A scoping review of access to thalidomide in Brazil suggested a need for a national Clinical Protocol and Therapeutic Guidelines for use of thalidomide in ENL cases, uniform accreditation of health centres approved for supply of thalidomide and for a national database of patients treated with it. Brazilian law requires women of childbearing age to use contraceptive precautions when they are prescribed thalidomide.…”
Section: Personal Communication)mentioning
confidence: 99%
“…The drug, infamously recognized in its devastating original form as a sedative and curative for morning sickness, returned to the medical world for the treatment of leprosy and, subsequently, multiple myeloma ( 5 ). It is worth noting that the discovery of thalidomide’s efficacy in treating leprosy, specifically erythema nodosum leprosum, was a serendipitous occurrence ( 6 ). The story behind this accidental discovery is recounted in the book Dark Remedy .…”
Section: Introductionmentioning
confidence: 99%